2011
DOI: 10.1002/hep.24128
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β adaptor, β2-spectrin, modulates cyclin dependent kinase 4 to reduce development of hepatocellular cancer

Abstract: Transforming growth factor beta (TGF-b) is an important regulator of cell growth, and loss of TGF-b signaling is a hallmark of carcinogenesis. The Smad3/4 adaptor protein b2-spectrin (b2SP) is emerging as a potent regulator of tumorigenesis through its ability to modulate the tumor suppressor function of TGF-b. However, to date the role of the TGFb signaling pathway at specific stages of the development of hepatocellular carcinoma (HCC), particularly in relation to the activation of other oncogenic pathways, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…One molecular mechanism for how liver cells can escape from the cytostatic TGF-β response was described by the work of Mishra and coworkers [14,15,16,17,18,19,20,21,22,23,24]. Initially, they found that disruption of the adaptor protein ELF, a β-spectrin, leads to disruption of TGF-β/Smad signaling.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…One molecular mechanism for how liver cells can escape from the cytostatic TGF-β response was described by the work of Mishra and coworkers [14,15,16,17,18,19,20,21,22,23,24]. Initially, they found that disruption of the adaptor protein ELF, a β-spectrin, leads to disruption of TGF-β/Smad signaling.…”
Section: Figmentioning
confidence: 99%
“…TGF-β triggers phosphorylation and association of ELF with Smad3 and Smad4, followed by nuclear translocation, therewith indicating an unexpected molecular link between a scaffolding protein and the TGF-β signaling pathway [24]. ELF-mediated TGF-β-dependent transcriptional responses are strongly related to its cytostatic response, comprising, for example, induction of p15, p21, MMP-9, p57, β-cadherin, and p16 expression as well as repression of β-catenin, c-myc, hTERT, IGF2, and LDLR transcription [14,18,20,21]. Additionally, PRAJA, a RING-H2 protein, was identified to interact with ELF leading to enhanced degradation via substantial E3-dependent ubiquitinylation.…”
Section: Figmentioning
confidence: 99%
“…Has also been proposed to be a differentiation marker in colonic neoplasia Reduced expression of spectrin associated with poor prognosis in pancreatic cancer and progression in hepatocellular cancer. Spectrin contributes to platinum chemotherapy resistance (Baek et al, 2011;Jiang et al, 2010;Kitisin et al, 2007;Maeda et al, 2011;Simpson and Page, 1992;Sormunen et al, 1994;Sormunen et al, 1999;Thenappan et al, 2009;Tuominen et al, 1996;Younes et al, 1989) Supervillin Stress fibres and focal adhesions of multiple cell types. Implicated in nuclear architecture…”
mentioning
confidence: 99%
“…These results are similar to those of previous studies investigating the tumor suppressive effects of TGF-β in liver cancer. Baek et al reported that TGF-β inhibited cell proliferation through cell cycle arrest (22). Senturk et al demonstrated that TGF-β induced downregulation of p21 (Cip1) and p15 (Ink4b) and inhibited cell proliferation through cell cycle arrest in HCC cell lines (23).…”
Section: Expression Of P-jnk P-c-jun and P-smad2 In Huh-7 And Huh-bamentioning
confidence: 99%